Studying the surface properties of high-molecular-weight membranes obtained by radiation polymerization; AIP Conference Proceedings; Vol. 2101 : Isotopes: Technologies, Materials and Application (ITMA-2018) - Sokhoreva V. V. Valentina Viktorovna; Dyusembekova A. A. Akbota Alibekovna; Golovkov V. M. Vladimir Mikhailovich; Sigfusson T. I. Torsteinn Ingi; Korneva O. S. Olga Sergeevna; Koptsev M. Maksim (2019, 2019)
Title screen